Wake Vortex Modelling and Simulation for Air Vehicles in Close Formation Flight - Saban, Deborah (Cranfield University, 2010)
The aim of this research is to develop realistic models of aerodynamic cross-coupling e ects that can be incorporated in real-time or near real-time simulations of Unmanned Aerial Vehicles (UAVs) in close formation flight. These would permit the assessment of the risks and issues associated with wake vortex evolution and encounter and the analysis of their consequences on the design of automatic control systems and the development of safe and reliable operating procedures. A number of wake vortex modelling techniques that can be used in formation flight simulations are reviewed. A novel Wake Vortex Model (WVM) is developed, implemented, verified, validated and successfully integrated within a Matlab/Simulink simulation environment. The code, named ELL because it is based on Weissinger’s extended lifting line theory, meets the following requirements: (i) it is generic and can easily be adapted to accomodate any wing planform and air vehicle configuration; (ii) it is computationally rapid enough to be used in real-time or near real-time simulations; (iii) and it is sufficiently representative to support studies of aerodynamic interaction between multiple air vehicles during formation reconfiguration and air-to-air refuelling simulations. Simulink test scenarios of two Aerosonde UAVs are developed to test and validate the use of ELL within simulation models, and the simulation environment is interfaced with visualisation tools in order to facilitate the evaluation of multiple air vehicle dynamic interaction.